2014
DOI: 10.2147/vmrr.s63805
|View full text |Cite
|
Sign up to set email alerts
|

Canine cerebrospinal fluid total nucleated cell counts and cytology associations with the prevalence of magnetic resonance imaging abnormalities

Abstract: Introduction:The combination of cerebrospinal fluid (CSF) analysis and magnetic resonance imaging (MRI) are often used to investigate intracranial disease in dogs. The aim of this retrospective study was to determine if the total nucleated cell count (TNCC) or cytology findings in abnormal CSF are associated with the prevalence of MRI abnormalities. Materials and methods: For each case, the TNCC was categorized into one of three groups:6 /L); and C (.100×10 6 /L). Cytology findings were categorized by the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In the study reported here, CSF cytology was not diagnostic for leukemia. The predominance of monocytoid cells and mixed pleocytosis observed in this study are non-specific and can be observed with any cause of CNS necrosis or myelomalacia and have been associated with various disease processes such as granulomatous meningoencephalitis, infectious agents (e.g., fungal, protozoal, or Ehrlichia ), and steroid-responsive meningitis; however, less frequently with meningioma ( 39 , 40 ). Flow cytometry was only performed on peripheral blood.…”
Section: Discussionmentioning
confidence: 55%
“…In the study reported here, CSF cytology was not diagnostic for leukemia. The predominance of monocytoid cells and mixed pleocytosis observed in this study are non-specific and can be observed with any cause of CNS necrosis or myelomalacia and have been associated with various disease processes such as granulomatous meningoencephalitis, infectious agents (e.g., fungal, protozoal, or Ehrlichia ), and steroid-responsive meningitis; however, less frequently with meningioma ( 39 , 40 ). Flow cytometry was only performed on peripheral blood.…”
Section: Discussionmentioning
confidence: 55%
“…The reason for not performing CSF collection was the potential for cerebellar herniation. Contraindications to CSF collection through the cerebellomedullary cistern are atlantoaxial subluxation, Chiari-like malformation, and the risk of cerebellar herniation through the foramen magnum [ 33 ]. Cats with brain herniation have a significantly lower level of consciousness in their Modified Glasgow Coma Scale score [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CSF analysis in dogs with spinal pathology is useful only when the results are correlated with the history, clinical findings and imaging studies (Dewey 2008;Lorenz et al 2011). To establish the diagnosis by this method is possible only in situations where microorganisms or neoplastic cells are identified in CSF samples (Musteata et al 2013;Hugo et al 2014).…”
Section: Lumbar Cerebrospinal Fluid Analysismentioning
confidence: 99%